PENGARUH KOMPETENSI DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. SAMAS BHAKTI PERTIWI MENGWI BADUNG - Tommy Andre Adi Putra; Ni Nyoman Suryani; Sapta Rini Widyawati (VALUES, 2021)
Performance is the real work achieved by a person in carrying out the tasks assigned to him in accordance with the vision, mission and goals set by the organization. Performance can be affected by competence and workload. This study aims to determine the effect of competence and workload on employee performance. The data collection method was done by using a questionnaire. The sample in this study were 50 respondents. Determination of the number of respondents is done through the census method. The data analysis technique used is the classical assumption test, multiple linear regression, the coefficient of determination test, t test and F test with SPSS software. The results of the instrument test showed valid and reliable data. The results showed that the competence and workload simultaneously affect the performance of employees at CV. Samas Bhakti Pertiwi. Competence has a positive and significant effect on employee performance at CV. Samas Bhakti Pertiwi. Workload has a negative and significant effect on employee performance at CV. Samas Bhakti Pertiwi.